Treatment of severe, chronic hand eczema: results from a UK‐wide survey. (1st March 2017) - Smith, I. L.; Brown, S.; Nixon, J.; Cowdell, F. C.; Ersser, S.; Fernandez, C.; Goodfield, M.; Green, C. M.; Hampton, P.; Lear, J. T.; Smith, C. H.; Sunderland, L.; et al.
Summary: Treatment of severe hand eczema (HE) that is resistant to topical potent corticosteroid treatment is challenging. In 2013, we surveyed 194 UK dermatologists to obtain information about their usual treatment pathways to inform the choice of the comparator in a trial of alitretinoin in severe HE (ALPHA trial); the results indicated that the treatment approaches favoured by UK dermatologists differ. Psoralen combined with ultraviolet A (PUVA) and alitretinoin were identified as the most frequent first‐line treatment options for hyperkeratotic HE, whereas oral corticosteroids were identified as the most frequent first‐line treatment for vesicular HE, followed by PUVA and alitretinoin. In terms of potential adverse effects of long‐term or repeated use, oral steroids and ciclosporin A were reported to cause most concern. There is uncertainty about which treatment gives the best short and long‐term outcomes, because of a lack of definitive randomised controlled trials evaluating the effectiveness of different treatment pathways in severe HE.